2007
DOI: 10.1111/j.1348-0421.2007.tb03892.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin‐10 on the Paracoccidioides brasiliensis Killing by Gamma‐Interferon Activated Human Neutrophils

Abstract: Paracoccidioidomycosis, a deep mycosis endemic in Latin America, is a chronic granulomatous disease caused by the fungus Paracoccidioides brasiliensis. Phagocytic cells play a critical role against this fungus, and several studies have shown the effects of activator and suppressive cytokines on macrophage and monocyte functions. However, studies on polymorphonuclear neutrophils (PMNs), that are the first cells recruited to the infection sites, are scarcer. Thus, the objective of this paper was to assess whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
(44 reference statements)
1
14
0
2
Order By: Relevance
“…We confirmed our previous studies showing that GM-CSF, IL-15, TNF-a and IFN-c activate human neutrophils inducing these cells to release higher H 2 O 2 levels and fungicidal activity against Pb [17,18,37]. However, both H 2 O 2 release and fungicidal Figure 3 Role of TLR2 and TLR4 on H 2 O 2 production.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We confirmed our previous studies showing that GM-CSF, IL-15, TNF-a and IFN-c activate human neutrophils inducing these cells to release higher H 2 O 2 levels and fungicidal activity against Pb [17,18,37]. However, both H 2 O 2 release and fungicidal Figure 3 Role of TLR2 and TLR4 on H 2 O 2 production.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown TLR2 and TLR4 requirement for cytokines production by phagocytic cells in response to several stimuli, including fungi. TLR4 is important for murine protection to C. albicans, by chemokines production such as KC and MIP-2, important for neutrophils influx [37]. Yet, in candidiasis, TLR2 is involved in TNF-a, MIP-2 [45], IL-12, IFN-c [46] and IL-10 production [47].…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence includes the following: (1) IL-10 knock-out mice infected with Trypanosoma cruzi and Toxoplasma gondii die rapidly because of a massive and sustained inflammatory response [129,130], and are predisposed to have an exaggerated Th1 immune response in the context of Plasmodium chabaudi chabaudi malaria [131] and Listeria monocytogenes meningoencephalitis [132]. (2) In contrast, elevated concentrations of IL-10, or an imbalance between IL-10 and IL-12 in favor of IL-10, have been associated with persistent infection-induced inflammation, resulting in the development of invasive and chronic disease, such as human visceral leishmaniasis [133], chronic human Candida albicans infections [134], as well as paracoccidioidomycosis [135][136][137][138][139][140]. (3) Upon LPS challenge, IL-10 deficient mice display an uncontrolled production of TNF-a [141], are extremely vulnerable to the generalized Shwartzman reaction [141], and are more sensitive to lethal acute endotoxin shock (which occurs with a 20-fold lower dose of LPS) [141].…”
Section: Il-10: a Cytokine That Dampens Inflammationmentioning
confidence: 99%
“…The proteins found to date have been determined by searching for differentially expressed genes participating in various metabolic pathways, the uptake and transport of metals such as iron, copper and zinc and the synthesis of virulence factors such as melanin and its precursors (Bailão et al, 2006;Costa et al, 2007;da Silva et al, 2006;Hamilton & Gomez, 2002;Ratledge & Dover, 2000;Taborda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%